MEMBANGUN WEBSITE PROGRAM STUDI ILMU KEPERAWATAN UNIVERSITAS SAHID SURAKART - Setiawan, Sukawati Novy; Anwariningsih, Sri Huning; Susilo, Dahlan (JURNAL GAUNG INFORMATIKA, 2017)
Nursing Science Sahid University of Surakarta is under the Faculty of Health  Sciences. The information about the major is still manual and not effective.  ccording to the improvement of information technology based on internet, website is the right  solution to convey information fast and eficiently. The purpose of this research is to  develop Nursing Science Sahid University of Surakarta website in order to simplify the  information management and delivery to the students and the society. The methods  which are used to collect the data are observation, interview, literature, and   questionnaire method to webQual test. The data analysis used is structured based on  Unified Modelling Language (UML). The making of this website uses HTML, PHP and  MySQL database programming. To measure the quality of the Nursing Science Sahid  University of Surakarta website, adjusted to the visitorsâ or the last userâs perception,  so the website test method used is webQual testing and Likert scale. From 30 questions  which were asked to 30 respondents and the data are processed using SPSS 20, the  testing result of the Nursing Science Sahid University of Surakarta website is 77,7%. It  means that the Nursing Science Sahid University of Surakarta website is good.